Mathematical puzzles - Winkler, P. (Peter), 1946- (Boca Raton : AK Peters/CRC Press, 2020)
"Research in mathematics is much more than solving puzzles, but most people will agree that solving puzzles is not just fun: it helps focus the mind and increase one's armory of techniques for doing mathematics. Mathematical Puzzles will, for the first time, make the connection explicit by isolating important mathematical methods, then using them to solve puzzles and prove a theorem. Features A collection of the world's best mathematical puzzles Each chapter features a technique for solving mathematical puzzles, examples, and finally a genuine theorem of mathematics that features that technique in its proof Puzzles that are entertaining, mystifying, paradoxical, and satisfying; they are not just exercises or contest problems"--
OCLC-licensed vendor bibliographic record.
Keywords: Mathematical recreations; MATHEMATICS / General; MATHEMATICS / Recreations & Games